Endovascular intervention in patients with blunt traumatic thoracic aortic injury: Early results - Hasan Toz; Yusuf Kuserli; Gulsum Turkyilmaz; Saygin Turkyilmaz; Ali Aycan Kavala (Turkish Journal of Vascular Surgery)
Aim: Mortality rates are high in thoracic aortic injuries caused by blunt trauma. Thoracic endovascular aortic repair (TEVAR) is the most commonly employed surgical strategy for patients with blunt traumatic thoracic aortic injuries (BTTAI) due to its favorable outcomes. This study aims to present our endovascular experience in treating Type B aortic dissections resulting from blunt trauma. Material and Methods: Our retrospective study included 70 patients who underwent TEVAR for Stanford Type B aortic dissection due to blunt aortic injury. Patients who were under 22 and over 70 years of age, those who underwent emergency TEVAR, died in a hospital emergency, and had penetrating aortic injury, head traumas with neurological symptoms and requiring intervention, aortic pathology other than Type B aortic dissection, or aortic rupture were excluded from the study. Results: Of the patients, 34.3% (n=24) were female, and 65.7% (n=46) were male, with a mean age of 48.54±10.00 years. The most common cause of injury was motor vehicle accidents (81.4%, n=57). No statistically significant difference was found between patients regarding the locations of the landing zones (p>0.05). Conclusion: Early outcomes in selected patients demonstrate high survival rates following TEVAR for trauma-induced Type B dissections. [Turk J Vasc Surg 2024; 33(3.000): 152-9]